Potential approaches for the pricing of cancer medicines across Europe to enhance the sustainability of healthcare systems and the implications. (4th July 2021) - Godman, Brian; Hill, Andrew; Simoens, Steven; Selke, Gisbert; Selke Krulichová, Iva; Zampirolli Dias, Carolina; Martin, Antony P; Oortwijn, Wija; Timoney, Angela; Gustafsson, Lars L; Voncina, Luka; Kwon, Hye-Young; et al.
ABSTRACT: Introduction : There are growing concerns among European health authorities regarding increasing prices for new cancer medicines, prices not necessarily linked to health gain and the implications for the sustainability of their healthcare systems. Areas covered : Narrative discussion principally among payers and their advisers regarding potential approaches to the pricing of new cancer medicines. Expert opinion : A number of potential pricing approaches are discussed including minimum effectiveness levels for new cancer medicines, managed entry agreements, multicriteria decision analyses (MCDAs), differential/tiered pricing, fair pricing models, amortization models as well as de-linkage models. We are likely to see a growth in alternative pricing deliberations in view of ongoing challenges. These include the considerable number of new oncology medicines in development including new gene therapies, new oncology medicines being launched with uncertainty regarding their value, and continued high prices coupled with the extent of confidential discounts for reimbursement. However, balanced against the need for new cancer medicines. This will lead to greater scrutiny over the prices of patent oncology medicines as more standard medicines lose their patent, calls for greater transparency as well as new models including amortization models. We will be monitoring these developments.